In vitro evaluation of a lentiviral two-step transcriptional amplification system using GAL4FF transactivator for gene therapy applications in bone repair. Issue 4 (July 2018) - Bougioukli, Sofia; Sugiyama, Osamu; Alluri, Ram; Yoho, Robert; Oakes, Daniel; Lieberman, Jay
Abstract In this study, we developed a lentiviral two-step transcriptional amplification (TSTA) system expressing bone morphogenetic protein-2 (BMP-2) under the control of a GAL4FF transactivator to enhance gene expression and limit toxicity for bone repair applications. To this end human MSCs, isolated from bone marrow or adipose tissue, were transduced overnight with a LV-TSTA system (GAL4FF or GAL4vp16) expressing BMP-2 or GFP and evaluated in vitro for transduction efficiency, mean fluorescence intensity, cell viability, and BMP-2 production. FACS analysis of GFP-transduced MSCs confirmed successful transduction with the GAL4FF+GFP vector. Moreover, ELISA demonstrated abundant BMP-2 production by GAL4FF+BMP2-transduced human MSCs over a period of 8 weeks, with minimal cytotoxicity at all time points. Compared to GAL4vp16, GAL4FF was superior with respect to BMP production at 1, 2, 4, 6, and 8 weeks in BMSCs. In ASCs, GAL4FF was still associated with higher BMP-2 production at weeks 2–8, but this difference was not as prominent as in BMSCs. To our knowledge, this is the first report of GAL4FF-mediated BMP-2 production by human BMSCs and ASCs. Compared to the standard GAL4vp16TSTA vector, GAL4FF was associated with lower cytotoxicity and higher in vitro gene expression in both BMSCs and ASCs.